Pengaruh Pertumbuhan Penduduk, Rasio Ketergantungan (Dependency Ratio) dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi di Samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The Purpose of this research to determine the effect of population growth, dependency ratio and the Human Development Index (HDI) of the Economic Growth in Samarinda. In this research used multiple linear regression analysis, but it is also aided with a computerized system using the software program SPSS (statistical package for service solution) version 21. After doing research with reference to the secondary data, it is concluded that there are three variables that affect economic growth that is population growth, dependency ratio, and Human Development Index (HDI). The results of the research simultaneously, variable population growth, dependency ratio and the Human Development Index (HDI) simultaneously affect impact on economic growth in Samarinda. Then, population growth and no significant negative effect on economic growth in Samarinda, dependency ratio and no significant negative effect on economic growth in Samarinda, and the Human Development Index and significant positive effect on economic growth in SamarindaKeywords : Economic growth population growth